Modificação de nanotubos de haloisita para preconcentração de metais em amostras de vinho - Santana, Allan Magalhães de (2019)
This work proposes the use of a hybrid nanosystem for the preconcentration of Pb+2 and determination by flame atomic absorption spectrometry (FAAS). The halloysite nanotube - HNTs underwent different exposure times to a phosphonic acid solution dietilenotriaminopentametileno - DTPMP, in view that these were to be functionalized. In order to verify under what conditions the functionalization would be more favorable, the work was carried out in two stages. In the first the commercial nanotubes were directly exposed to DTPMP; in the second step, they were initially purified with hydrogen peroxide and then half of this material was treated with NaOH solution and the other half treated with HCl solution, only to be exposed to DTPMP. The system was refluxed and kept under stirring in a glycerin bath at 100 ° C for 5h, 15h, and 25h intervals. The samples were characterized by X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), thermogravimetric (TG) analysis, elemental analysis, nitrogen adsorption / desorption, Scanning Electron Microscopy (SEM) and Microscopy Transmission Electronics (TEM). The XRD results show that the different samples did not show changes in the diffraction pattern, with the Al2Si2O5(OH)4 major phase. The structure and morphology of the different HNT samples were characterized by SEM showing cylindrical tubes with a diameter in the range of 40 to 70 nm and a length of up to 2 μm. The images obtained through the TEM are in agreement with SEM. The interaction between HNTs and DTPMP was confirmed by the techniques of FTIR, TG, elemental analysis and nitrogen adsorption and desorption. From the results of the characterizations, it can be observed that the methodology proposed for functionalization of the HNTs with DTPMP was successful. To determine the preconcentration efficiency standard solutions of Pb were subjected to the same method with different materials synthesized in the work, using as reference the material without functionalization. The modified HNT showed promising adsorbent material for the removal of Pb+2 in samples pre-concentrated with the metal, since it presented recovery percentage between 85 and 110%.